2020
DOI: 10.1038/s41567-020-0791-2
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic patterns of interacting contagions are indistinguishable from social reinforcement

Abstract: From fake news to innovative technologies, many contagions spread via a process of social reinforcement, where multiple exposures are distinct from prolonged exposure to a single source. Contrarily, biological agents such as Ebola or measles are typically thought to spread as simple contagions. Here, we demonstrate that interacting simple contagions are indistinguishable from complex contagions. In the social context, our results highlight the challenge of identifying and quantifying mechanisms, such as social… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 51 publications
2
54
0
1
Order By: Relevance
“…Specifically, we must remember that distributions of secondary cases, just like R 0 itself, are just as much a product of a pathogen as of the population in which it spreads. For example, aspects of the social contact network [ 44 ], metapopulation structure [ 45 ], human mobility [ 46 ], adaptive behaviour [ 47 ] and even other pathogens [ 48 , 49 ] all interact to cause complex patterns of disease emergence, spread and persistence. Therefore, great care must be taken when using any of these tools to compare outbreaks or to inform current events with past data.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we must remember that distributions of secondary cases, just like R 0 itself, are just as much a product of a pathogen as of the population in which it spreads. For example, aspects of the social contact network [ 44 ], metapopulation structure [ 45 ], human mobility [ 46 ], adaptive behaviour [ 47 ] and even other pathogens [ 48 , 49 ] all interact to cause complex patterns of disease emergence, spread and persistence. Therefore, great care must be taken when using any of these tools to compare outbreaks or to inform current events with past data.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we must remember that distributions of secondary cases, just like R 0 itself, are just as much a product of a pathogen as of the population in which it spreads. For example, aspects of the social contact network [27], metapopulation structure [28,29], mobility [30,31], adaptive behavior [32,33], higher-order contact structure [34,35], and even other pathogens [36,37], all interact to cause complex patterns of disease emergence, spread, and persistence. Therefore, great care must be taken when using any of these tools to compare outbreaks or to inform current events with past data.…”
Section: Discussionmentioning
confidence: 99%
“…information and inflammatory content, for example during political events 8,30,37,38 , remain fundamentally unknown. Recently, it has been suggested that this challenging phenomenon might exist because, at a population level, the dynamics of multiple interacting contagions are indistinguishable from social reinforcement 39 .…”
Section: Assessing the Risks Of 'Infodemics' In Response To Covid-19 mentioning
confidence: 99%